2015
DOI: 10.5897/jene2015.0532
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to delineation of the eco-climatic zones in Northern Nigeria

Abstract: This study derived eco-climatic indices; a moisture quality index, onset and cessation dates, hydrologic growing season and Aridity Index all for the period (1950-2006), in addition to using National Oceanographic and Atmospheric Administration an Advanced Very High Resolution Radiometer images to derive a Soil Adjusted Vegetation Index map. These derived eco-climatic parameters were integrated using Geographic Information System (GIS) techniques. The overlay was hinged on a theoretical basis which holds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Reductions in indices were mostly observed in the eastern and western axis while locations southward of the basin showed more of no change in vulnerability indices than slight reductions. This tallies with the study conducted by [39] which showed that changes in climate and biodiversity of the northwest of Nigeria are initiating a shift in its ecological delineation.…”
Section: Changes In Vulnerabilitysupporting
confidence: 82%
“…Reductions in indices were mostly observed in the eastern and western axis while locations southward of the basin showed more of no change in vulnerability indices than slight reductions. This tallies with the study conducted by [39] which showed that changes in climate and biodiversity of the northwest of Nigeria are initiating a shift in its ecological delineation.…”
Section: Changes In Vulnerabilitysupporting
confidence: 82%
“…It is bordered to the north by Niger Republic, to the east by Republic of Cameroun, to the south by the tropical rainforest and to the west by Benin Republic. The two predominant air masses that influence the weather and climate of these zones are Tropical Continental (cT) air mass and Tropical Maritime air mass (mT) [12]. The former is dry and dusty which originates from Sahara Desert, while the latter is dense and moist which originates from Atlantic Ocean.…”
Section: Methodsmentioning
confidence: 99%
“…The end of the rainy season is followed by a period of cold, dry, dusty and hazy atmospheric conditions, a weather condition known as the Harmattan from the Sahara Desert, which could last for two to three months. This activity of the wind lowers temperatures considerably saving inhabitants for some time from the scorching heat that would have occurred as a result of clearer skies during the dry season (Sharu et al 2013, AbdulKadir et al 2015. Generally, the soils are developed from acidic metamorphic rocks and have low activity kaolinite clay.…”
Section: Methodsmentioning
confidence: 99%